Phase-Field Crystals : Fast Interface Dynamics. - Galenko, Peter (De Gruyter Studies in Mathematical Physics Ser., 2018)
The Phase Field Crystal (PFC) model incorporates microscopic structural details into a mesoscopic continuum theory. Methods for fast propagation of PFC interfaces are discussed in this book. They can handle a wide range of thermal gradients, supersaturations and supercoolings, including applications such as selective laser melting. The reader will find theoretical treatment in the first half, while the latter half discusses numerical models.